Polypharmacology in Drug Discovery: A Review from Systems Pharmacology Perspective - Zhang, Wenjuan; Bai, Yaofei; Wang, Yonghua; Xiao, Wei (Current Pharmaceutical Design, 2016)
Background: The complexity of diseases has led to recent interest in polypharmacology, which suggests that many effective drugs specially modulate multiple targets. Drugs with multiple targets can provide a superior therapeutic effect and decrease in side effect profile compared to ligands with single target, especially in the treatment of complex diseases, such as tumors, nervous system diseases and inflammatory diseases. The network-based polypharmacology holds the promise of expanding the opportunity for novel targets and drug identification. However, it faces considerable challenges to how multi-target drugs can be rationally designed from the network pharmacology perspective, particularly for combinations of targets that are structurally divergent. Methods: In this review, we focus on the pharmacological properties of current polypharmacology, discuss potential novel drug indication arising from drug repurposing, and introduce approaches to the rational design of multi-target drugs. Results: As a result, we highlighted the features of polypharmacology. Also, we have presented some computational methods to predict the potential novel multi-target drugs with lower toxicity and higher efficacy. Moreover, network analysis might play important role in repositioning drugs that modulate targets involved in different pathologies. Conclusion: This perspective aims to provide a global view on polypharmacology, which is the foundation of the next paradigm in drug discovery.
Keywords: multi-target drugs